"Powered Cheese Wire Technique" for Septal Fenestration in Complex Endovascular Repair for Chronic Thoracoabdominal Aortic Dissection. (October 2021) - Gandet, Thomas; Alushi, Kastriot; Westermann, Dirk; Schirmer, Johannes; Rohlffs, Fiona; Panuccio, Giuseppe; Kölbel, Tilo
Purpose: Endovascular repair of chronic thoracoabdominal aortic dissection with aneurysmal degeneration presents a therapeutic challenge when one or more visceral branches arise from the false lumen without an adjacent reentry. The chronic dissection flap can be thick and resistant to flap fenestration with standard techniques. Technique: The powered cheese wire technique facilitates cutting of a dissection flap using electrical current on a noninsulated through-and-through wire segment. The mid-shaft of the guidewire is denuded and kinked to form the "flying V" configuration. This solution is based on the BASILICA procedure, which uses electrosurgery to split aortic valve tissue lengthwise prior to transcatheter aortic valve replacement to prevent coronary artery obstruction. We demonstrate the technique in a case of branched endovascular aortic repair of a complex thoracoabdominal dissecting aneurysm in which a renal artery from the false lumen was catheterized by creating a powered cheese wire fenestration. Conclusion: The powered cheese wire technique is an effective approach to access false lumen originating branches during endovascular aortic repair of chronic aortic dissections.